Dejavniki, pomembni za uporabnike ortopedskih čevljev in njihove prilagoditve - Štajer, Tomaž (Rehabilitacija (Ljubljana), 2015)
Background: The aim of our study was to find out which factors, and in what ranking order, are important for the satisfaction of users of orthopaedic shoes in Slovenia. We also wanted to establish whose opinion on orthopaedic shoes is the most important for the users and whether the orthopaedic shoes reduce foot pain and walking problems. In addition, we surveyed the types of adjustments and the differences in adjustments with respect to shoe type. Methods: The patients who visited the outpatient clinic for complex foot deformities at the University Rehabilitation Institute in Ljubljana in 2013 and had been wearing custom-made orthopaedic shoes for at least one year were asked to fill in a survey on the importance of various factors for user satisfaction, which was designed based on published research. The collected data were statistically analysed. Results: The survey included 128 persons aged 12 to 92 years who had been using orthopaedic shoes for 1 to 67 years. Forty-nine persons were using custom-made standard shoes, 58 were using custom-made standard shoes with foot orthosis designed and manufactured by plaster-casting ("advanced type"), and 21 were using shoes designed and manufactured by plaster casting ("the most advanced type"). The participants ranked comfort the highest, followed by durability. The least important factor was other people's opinion. Orthopaedic shoes significantly reduced foot pain (average rating on 0-10 scale diminished from 5.9 to 2.7, p<0.001) and walking problems (average rating on 0-10 scale diminished from 8.1 to 2.1, p<0.001). The more advanced the shoes, the more adjustments were required, and the types of adjustments statistically significantly differed (p<0.001) with respect to the type of shoes. Conclusion: Shoe comfort is the most important factor for satisfaction of the users of orthopaedic shoes in Slovenia. Orthopaedic shoes successfully reduce foot paint and walking problems.
Keywords: adjustments; ankete; čevlji; Orthopedics; ortopedija; ortopedski čevlji; prilagoditve; Shoes; Surveys and Questionnaires; user satisfaction; vprašalniki; zadovoljstvo uporabnikov